SERVICII INOVATIVE LA BIBLIOTECA „ȘTEFAN CEL MARE” - BEȘAN, șef oficiu, Filiala „Ștefan cel Mare”, Lilia (BIBLIOPOLIS, 2020)
The „Stefan cel Mare” Branch has launched four projects aimed to promote books and reading: the erudition contest Become famous with Romanian writer, the Club of young poets. The game the Wonder wheel and the workshop The Theatre at the library. The „Ștefan cel Mare” Branch became an important culture place for the community, where the users can raise the level of knowledge, can evolve both intellectually and civic; have the chance to discover the intellectual competition, becoming stars. These activities contribute to the stimulation of the intellectual freedom and respond to the users’ requests, being an environment for the lifelong learning and interpersonal communication.